Race in Early Modern England - Burton, J. author. aut Link
XVII, 300 p.
Keywords: This collection makes available for the first time a rich archive of materials that illuminate the history of racial thought and practices in sixteenth and seventeenth century England. A comprehensive introduction shows how these writings are crucial for understanding the pre-Enlightenment lineages of racial categories.